Pengaruh Financial Knowledge, Hedonism Lifestyle Dan Self Control Terhadap Financial Behavior - Fitriani, Nur Afika; Mardani, Ronny Malavia; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to identifying and analyze the influence between financial knowledge, hedonism lifestyle and self control on financial behavior. This research uses studies on gen Z in Ketapang sub-district, Sampang district, east java. A total of 80 participants in this research. The analytical method used in this research was intstrument test that is validity test and realibility test, mormality test, classic assumption test analysis that is multicolinearity test and heteroskedasticity test, multiple linear regression analysis, hypothesis test that is F test, t test and coefficient of determination test using SPSS data processing. This research states the results that financial knowledge has a significantly positive effect on financial behavior, hedonism lifestyle has a significantly positive effect on financial behaviorand self control has a significantly positive effect on financial behavior. Keywords: financial knowledge, hedonism lifestyle, self control and financial behavior